Binge Drinking in Young University Students Is Associated with Alterations in Executive Functions Related to Their Starting Age. - Diana Salas-Gomez; Mario Fernandez-Gorgojo; Ana Pozueta; Isabel Diaz-Ceballos; Maider Lamarain; Carmen Perez; Pascual Sanchez-Juan (PLoS ONE, 2016)
Our aim was to evaluate whether or not alcohol consumption in the form of binge drinking is associated with alterations of memory and executive functions in a population of university students. At the same time, we have studied the role of potential modulating factors, such as the APOE genotype or physical exercise.University students enrolled in academic year 2013-2014 at Escuelas Universitarias Gimbernat-Cantabria, affiliated with the University of Cantabria, were invited to participate in the study. We gathered sociodemographic data and details regarding the lifestyle of 206 students (mean age 19.55 ± 2.39; 67.5% women). We evaluated memory and executive functions via a series of validated cognitive tests. Participants were classified as binge drinkers (BD) and non-BD. Using Student's t-distribution we studied the association between cognitive tests and BD patterns. Multivariate analyses were carried out via multiple linear regression. 47.6% of the students were found to be BD. The BD differed significantly from the non-BD in their results in the executive functions test TMT B (43.41 ± 13.30 vs 37.40 ± 9.77; p = 0.0003). Adjusting by age, sex, academic records, age at which they started consuming alcohol, cannabis consumption, level of physical activity and other possible modifying variables, the association was statistically significant (p = 0.009). We noticed a statistically significant inverse correlation (Pearson's r2 = -0.192; p = 0.007) between TMT B and starting age of alcohol consumption. Differences were observed in another executive functions test, TMT A, but only in the group of women (19.73±6.1 BD vs 17.78±5.4 non-BD p = 0.05). In spite of the young age of our participants, BD was associated with a lower performance in the executive functions test (TMT B). These deficits were related to the age at which they started drinking alcohol, suggesting an accumulative effect.